ANALISIS PROSES REKRUTMEN, SELEKSI DAN PENEMPATAN KARYAWAN DI PT MRT JAKARTA - Handoko Handoko (JURNAL AGHNIYA, 2020)
abstract The purpose of this study is to analyze the recruitment process, selection and employee placement at PT MRT Jakarta. The process of recruitment, selection and placement of employees at PT MRT Jakarta refers to the Standard Operational Procedure (SOP) for recruitment and SOP for employee selection and placement. The results of field observations in June 2019 during the recruitment the candidate of employees at PT MRT Jakarta that conducted at Indonesian Railroad Polytechnic showed 90 graduates of the Indonesian Railroad Polytechnic were enthusiastic joined the selection process through the psychological testing stage which was held on June 22, 2019. This research is a descriptive qualitative research. The primary data collection procedure was carried out by in-depth interviews with the candidate of employees, managers of MRT, and team recruitment. The secondary data is taken from MRT management and the technique in determining informants is done by snowball sampling method. The results of this study indicate that the recruitment process at PT MRT Jakarta are in accordance with operational standards (SOP). Based on the results of the questionnaire is given to 90 respondents taken from a number of the candidate of employee who joining the test 78% of respondents stated that they were very satisfied with the test process conducted by MRT Jakarta, 10% of respondents satisfied with the test process, 6.25% of respondents are not satisfied, 4% respondents very not satisfied with the test. The data showed that the recruitment process that conducted by PT MRT Jakarta were effective. Keywords: recruitment, selection, replacement Abstrak Tujuan dari penelitian ini adalah untuk menganalisis proses rekrutmen, seleksi dan penempatan karyawan di PT MRT Jakarta. Proses rekrutmen, seleksi dan penempatan karyawan di PT MRT Jakarta mengacu pada Prosedur Operasional Standar (SOP) untuk rekrutmen dan SOP untuk seleksi dan penempatan karyawan. Hasil pengamatan lapangan pada Juni 2019 saat rekrutmen calon karyawan di PT MRT Jakarta yang dilakukan di Politeknik Kereta Api Indonesia menunjukkan sekitar 90 lulusan Politeknik Kereta Api Indonesia antusias mengikuti proses seleksi melalui tahap pengujian psikologis yang diadakan pada 22 Juni 2019. Penelitian ini adalah penelitian kualitatif deskriptif. Prosedur pengumpulan data primer dilakukan dengan wawancara mendalam dengan kandidat karyawan, manajer MRT, dan perekrutan tim. Data sekunder diambil dari manajemen MRT dan teknik dalam menentukan informasi dilakukan dengan metode snowball sampling. Hasil penelitian ini menunjukkan bahwa proses rekrutmen di PT MRT Jakarta sudah sesuai dengan standar operasional (SOP). Berdasarkan hasil kuesioner yang diberikan kepada 90 responden yang diambil dari sejumlah calon karyawan yang mengikuti tes 78% responden menyatakan bahwa mereka sangat puas dengan proses pengujian yang dilakukan oleh MRT Jakarta, 10% responden puas dengan proses pengujian, 6,25% responden tidak puas, 4% responden sangat tidak puas dengan tes. Data menunjukkan bahwa proses rekrutmen yang dilakukan oleh PT MRT Jakarta efektif. Kata kunci: rekrutment, seleksi, dan penempatan